Pluralism in Religion: Perspectives of Karen Armstrong and Husein Ja'far Al Hadar: Pluralisme Agama: Perspektif Karen Armstrong Dan Husein Ja’far Al Hadar - Wisnu Gautama (urn:alkarim://2988-795Xalkarim.v3i3)
Religious pluralism remains a central theological issue, particularly concerning claims of salvation across different faiths. This article aims to compare the perspectives of Karen Armstrong and Husein Ja’far Al Hadar as representatives of two contrasting approaches to the concept of salvation in the context of religious pluralism. Using a qualitative approach and library research method, this study examines the primary works of both figures and relevant secondary literature. The findings indicate that Armstrong, through her inclusive approach, asserts that all religions embody universal values that may lead to salvation. In contrast, Husein Ja’far emphasizes the exclusivity of salvation within Islam while still promoting tolerance and respect for religious diversity. These differing views are shaped by the social and epistemological backgrounds of each thinker. This article contributes to the enrichment of religious pluralism discourse and strengthens the contextual interfaith tolerance narrative in Indonesia